GREENWASH Impact Analysis : How This Affects Consumer Purchase Intention towards Eco-Friendly Drinking Water Products in rPET Plastic Bottles - Ade Irwan Mulyana; Permana, Dudi (Dinasti Publisher, 2024)
Growing environmental awareness has triggered a significant shift in consumer purchasing preferences in Indonesia. Consumers now tend to choose green products that have minimal impact on environmental damage. This study was conducted to examine the influence of Greenwash, Green Skepticism, Green Trust on Green Purchase Intention as well as the mediation effect produced and how information and knowledge can moderate Greenwash on Green Purchase Intention on consumers of bottled drinking water products (AMDK) recycled plastic bottles PET. This type of research is a quantitative approach using primary data with a sample of 129 respondents. The sampling technique used is purposive sampling. The data collection method used is an online questionnaire. The approach used in this study is the Structural Equation Model (SEM) with the Smart-PLS 3.2.9 analysis tool. The results showed that Greenwash had a positive effect not significantly on Green Purchase Intention but was significant on Green Skepticism and had a significant negative effect on Green Trust. Green Skepticism also plays a significant role in influencing Green Purchase Intention. Green Trust has a non-significant positive effect on Green Purchase Intention. As a mediator, Green Skepticism fully mediates Greenwash and Green Purchase Intention, while Green Trust does not act as a mediator. Information and Knowledge does not moderate the influence of Greenwash on Green Purchase Intention on rPET bottled water products.